Home » Simplify the given expression (sqrt{frac{1 – cos x}{1 + cos x}})

Simplify the given expression (sqrt{frac{1 – cos x}{1 + cos x}})

Simplify the given expression (sqrt{frac{1 – cos x}{1 + cos x}})
  • A.
    (frac{1 – cos x}{sin x})
  • B.
    1 – cos x
  • C.
    sin x
  • D.
    1 + cos x
  • E.
    (frac{1 + cos x}{sin x})
Correct Answer: Option A
Explanation

(sqrt{frac{1 – cos x}{1 + cos x}}) = a
a2 = (frac{1 – cosx}{1 + cosx})
(frac{1 – cosx}{1 + cosx}) = (frac{1 – cosx}{1 – cosx})
= (frac{(1 – cosx)^2}{cos^2 x})
a2 = (frac{(1 – cos x)^2}{sin^2 x})
a = (frac{1 – cos x}{sin x})